Pengaruh Literasi Keuangan Terhadap Keputusan Investasi Pasar Modal Pada Mahasiswa Universitas Islam Negeri Sumatera Utara - Yulpida Sari Lubis; Zamzami Akromi Lubis; Zulfa Khoiriah; Muhammad Ikhsan Harahap (Jurnal Riset Ekonomi dan Akuntansi, 2023)
The goal of the study is to ascertain how investing decisions are impacted by financial literacy. The investment activity of investing produces revenue both now and in the future. Investors should research and comprehend the greatest investments before making a decision. To avoid being duped, most consumers lack basic investment knowledge. As a result, those who are financially literate may prevent mistakes and comprehend the dangers involved. The research method uses inferential statistics in a quantitative way. Instrument tests, such as the traditional assumption test and the basic linear regression test with partial test (t-test), were used to conduct data analytic procedures. The investigation' findings demonstrate that financial literacy significantly and favorably affects investing choices, This demonstrates that a person can invest more easily and understandably the more financially literate they are.